Processamento e aquisição das relações correferenciais: uma investigação sobre as relações entre linguagem e memória de trabalho em crianças e adultos - Araújo, Angela Maria de (2019)
The processing of co-referential relationships has received considerable attention in recent years. Indeed, a large number of papers have investigated questions concerning how speakers process the various co-forms, especially in anaphoric resolutions. In Brazilian Portuguese (PB), studies of Ferrari-Neto and Marinho (2015) and Grolla (2010, 2012) can be cited. These studies have provided important data on the co-referential processing and its acquisition, although they have not focused specifically on the investigation of the relationship between linguistic knowledge, defined in the form of an internalized grammar, and the systems that support it, among which the working memory. This paper aims to address this relation. By means of one experiment, based on memory and reading task, it was tried to provide fundamentals about the relation between the working memory functioning and its information retention / retrieval capacity with the processing / acquisition of the antecedent of the pronoun “ele”, controlling the number of sentences intervening between the pronoun and the antecedent and, a task of reading texts. The experiments drew on written stimuli presented in the form of texts. Six-, seven-, eight- and nine-year-old participants were tested in a normal acquisition process of Brazilian Portuguese, as well as native speakers of PB. All participants, adults and children, were selected based on their reading competence through the application of a Cloze test. The results showed a positive correlation between the number of intervening sentences and the processing time, thus suggesting that a higher load in the working memory affects the anaphoric processing. It has also been verified that there is a chronological progressive maturation of both the working memory and the grammar, which affects the processing of the antecedents. The results of the experiment provided further evidence on the capacity of working memory and its relation to linguistic processing.